Sepenuh Hati Menggapai Asa Untuk Mewujudkan PTMT Di Sekolah Saat Pandemi Covid - 19 - Sri Kis Untari (Universitas PGRI Adi Buana Surabaya, 2022)
Seeing the many benefits that will be gained from reading a lot. So it is important for teachers and education personnel to read, but not everyone has an interest in reading. Based on the results of observations made by researchers that interest in reading does not go well because teachers and students are not able to focus on reading material. Starting from the things above, the researchers will take a suitable school action to overcome these problems as a solution to make teachers and students active, motivated, and enthusiastic in reading. Therefore, the researchers formulated it into a school action research report entitled: